Using the particle finite element method for predicting edge-cracking in complex phase high-strength steel sheets - Sandin Olle; Larour Patrick; Rodríguez Juan Manuel; Kajberg Jörgen; Casellas Daniel (MATEC Web of Conferences)
Advanced High-strength steel (AHSS) sheets enable lightweight designs by reducing material thickness while retaining necessary structural properties. However, their high strength often complicates forming operations and increases vulnerability to defects such as edge-cracking, commonly initiated during shear cutting which is performed before forming. Existing forming limit analyses fall short in accounting for damage at the sheared edge, underscoring the demand for advanced simulation tools. This study explores the use of the Particle Finite Element Method (PFEM) to model shear cutting in AHSS sheets, focusing on its potential to improve understanding of edge damage and its effects on subsequent formability. By addressing challenges like mesh distortion and the accurate transfer of stress and strain data during particle re-connectivity, PFEM ensures that critical residual information at the cut edge is retained, facilitating reliable assessments of its formability and durability. The presented PFEM framework predicts optimal cutting conditions for specific AHSS grades by evaluating edge characteristics, such as roll-over, burnish, fracture, and burr, across various clearances. Validation of the simulation results is achieved through experimental hole expansion tests, highlighting the model's effectiveness in predicting the cut edge characteristics relating to the edge-cracking phenomenon.